2003
DOI: 10.1161/01.str.0000058157.69113.f6
|View full text |Cite|
|
Sign up to set email alerts
|

Changes Related to Age and Cerebrovascular Symptoms in the Extracellular Matrix of Human Carotid Plaques

Abstract: Background and Purpose-Many processes involved in the pathogenesis of atherosclerosis result in modifications of the extracellular matrix. These changes not only determine the mechanical stability of atherosclerotic lesions but can directly or indirectly influence further development of the lesions. The purpose of the present study was to compare the matrix composition of human carotid plaques from symptomatic patients with those obtained from patients without symptoms. Furthermore, matrix changes related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 31 publications
1
53
1
5
Order By: Relevance
“…However, the soluble elastin that we investigated in the present study of aortic specimens showed a decreasing pattern, which is different from the other elastin-associated proteins previously described. 14,[24][25][26][27][28] In the present study, we found that in the non-atherosclerotic aorta soluble elastin was (1) distributed both within the intima and around the mature elastin within the media, (2) different from mature elastic fiber (Figure 1), (3) had the lowest mRNA expression among the 4 histological groups (Figure 3d), (4) present in a low ratio to tropoelastin, which is conjectured to be a marker of elastin synthesis, compared with ruptured plaque (Figure 5), and (5) associated with the activity of MMP-9 among the 4 groups (Figure 3b). These results indicate that in the non-atherosclerotic aorta from subjects approximately 53-84 years of age, soluble elastin is densely distributed and neither endogenous elastogenesis or elastolysis is activated excessively, so soluble elastin may be deposited gradually and preserved within the intima and around the mature elastic fibers within the media over a number of years because the intima is not diseased.…”
Section: Discussionmentioning
confidence: 99%
“…However, the soluble elastin that we investigated in the present study of aortic specimens showed a decreasing pattern, which is different from the other elastin-associated proteins previously described. 14,[24][25][26][27][28] In the present study, we found that in the non-atherosclerotic aorta soluble elastin was (1) distributed both within the intima and around the mature elastin within the media, (2) different from mature elastic fiber (Figure 1), (3) had the lowest mRNA expression among the 4 histological groups (Figure 3d), (4) present in a low ratio to tropoelastin, which is conjectured to be a marker of elastin synthesis, compared with ruptured plaque (Figure 5), and (5) associated with the activity of MMP-9 among the 4 groups (Figure 3b). These results indicate that in the non-atherosclerotic aorta from subjects approximately 53-84 years of age, soluble elastin is densely distributed and neither endogenous elastogenesis or elastolysis is activated excessively, so soluble elastin may be deposited gradually and preserved within the intima and around the mature elastic fibers within the media over a number of years because the intima is not diseased.…”
Section: Discussionmentioning
confidence: 99%
“…10 Informed consent was given by each patient. The study was approved by the local ethical committee.…”
Section: Patientsmentioning
confidence: 99%
“…Plaques were weighed, homogenized, and elastin, collagen, and sulfated glycosaminoglycans (GAG) were determined as described previously. 3 …”
Section: Computed Tomographymentioning
confidence: 99%